Analisis Lubang Bukaan Decline Channel (CH) 677 Blok Cikoneng PT. Cibaliung Sumberdaya, Banten - Annisa Hanim D; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Study was conducted in the underground mine of PT Cibaliung Sumberdaya, Cimanggu, Pandeglang, Banten Province. Openings of declines and mining fronts, has caused the stability of the mining area to be disrupted. Rock deformation at the site is decline still observed using a convergence meter. In detail the observation area was carried out at decline Cikoneng CH 677, the rock mass quality (RMR) is 31 and width of decline is 4,2 m. From the results of the observation, the CH 677 have a lump on the left wall and cracks on shotcrete. The cumulative convergence monitoring results show a displacement is 32,285 mm with the largest displacement speed of 1,718 mm/day. The 2 D modeling results based on convergence theory, the area are categorized as unstable. For this reason, the stability of the aperture hole was performed using software Phase 2 with Hoek-Brown collapse criteria. The simulation produced a support system using 5 pieces of rock bolt (2,4 m) set of on the left wall with a space of 0,8 m, 5 pieces on the right wall with a spacing of 0,8 m and using shotcrete on the left wall with a thickness of 100 mm.Keywords: Decline, convergence meter, tunnel stability, deformation, rock bolt